Analysis of Receivables Turnover at PT. Primarindo Asia Infrastructure Tbk Bandung 2019-2021 Period - Adinda, Luthfiana; Nurhayati (Journal of Economic Empowerment Strategy (JEES), 2024)
PT Primarindo Asia Infrastructure Tbk Bandung, a company specializing in the production and marketing of sports/casual footwear, has faced fluctuations in receivables and an annual increase in provisions for the impairment of receivables during the period 2019-2020. This indicates challenges in receivables management and an escalation of the risk of payment failure by debtors. The objective of this research is to analyze receivables turnover and identify obstacles as well as efforts made by PT Primarindo Asia Infrastructure Tbk Bandung in addressing receivables turnover issues. This research utilizes a descriptive quantitative approach to analyze data by illustrating situations using numerical figures, which are subsequently analyzed to present research findings in the form of a research report. Data collection methods involve non-participant observation and interviews. Data analysis techniques use receivables turnover ratios and average collection periods, applying evaluation standards based on Kasmir's theory. Based on the research findings, it is revealed that receivables turnover from 2019 to 2021 is below the evaluation standard set by Kasmir's theory, stating that the ideal receivables turnover is around 15 times.